Advanced technique of catalytic ozonation-enhanced coagulation for the efficient removal of low coagulability refractory organics from secondary effluent. (September 2022) - Qiu, Jin-Li; Li, Da-Wei; Jing, Shi-Chao; Qiu, Huan; Liu, Fu-Qiang
Abstract: The novel cascaded catalytic ozonation-enhanced coagulation process (FeCeAC/O3 -PAC) was developed with much success towards second effluent organic matter (EfOM) in chemical industrial wastewater. Compared with the conventional techniques, FeCeAC/O3 -PAC exhibited remarkable performances in the advanced removal of EfOM. The characteristics of EfOM and interactivities of reaction process played the crucial roles. Especially, the removal rate constant of soluble microbial products (SMPs) with FeCeAC/O3 -PAC exceeded 55.38% versus FeCeAC/O3 . The outstanding synergistic effect was contributed to the enhanced generation of active oxygen species by FeCeAC and PAC, which increased the content of oxygen-containing functional groups of EfOM and thus facilitated the interaction between PAC and EfOM. As the result, the larger-sized flocs could be formed and separated easily. Herein, this work found a far more effective way to remove EfOM especially low-coagulability refractory organics (LCRO) in chemical sewage plant. Graphical abstract: Image 1 Highlights: FeCeAC catalyst and PAC can effectively decompose O3 . FeCeAC/O3 -PAC enhanced the removal kinetics of fluorescent components. The binding sites for EfOM and PAC could be increased by catalytic ozonation.